Increased Bilateral Interactions in Middle-Aged Subjects - Heetkamp, Jolien; Hortobagyi, Tibor; Zijdewind, Inge (Frontiers in Aging Neuroscience, 2014)
A hallmark of the age-related neural reorganization is that old vs. young adults execute typical motor tasks by a more diffuse neural activation pattern including stronger ipsilateral activation during unilateral tasks. Whether such changes in neural activation are present already at middle age and affect bimanual interactions is unknown. We compared the amount of associated activity, i.e., muscle activity and force produced by the non-task hand and motor evoked potentials (MEPs) produced by magnetic brain stimulation between young (mean 24 y, n = 10) and middle-aged (mean 50 y, n = 10) subjects during brief unilateral (7 levels of % maximal voluntary contractions, MVC) and bilateral contractions (4 x 7 levels of % MVC combinations), and during a 120-s-long MVC of sustained unilateral index finger abduction. During the force production the excitability of the ipsilateral (iM1) or contralateral (cM1) primary motor cortex was assessed. The associated activity in the ‘resting’ hand was ~2-fold higher in middle-aged (28% of MVC) vs. young adults (11% of MVC) during brief unilateral MVCs. After controlling for background muscle activity, MEPs in iM1 were similar in the two groups during brief unilateral contractions. At low (bilateral) forces only, MEPs evoked in cM1 were 30% higher in the middle-aged vs. young adults. At the start of the sustained contraction, the associated activity was higher in the middle-aged vs. young subjects and increased progressively in both groups (30% vs. 15% MVC at 120 s, respectively). MEPs were greater at the start of the sustained contraction in middle-aged subjects but increased further during the contraction only in young adults. Under these experimental conditions, the data provide evidence for the reorganization of neural control of unilateral force production as early as age 50. Future studies will determine if the altered neural control of such inter-manual interactions are of functional significance.